Belated Arabo-Islamic difference in excess: racialised religious practice under modernity/coloniality in Lebanon - Kassem, Ali M. (Journal of contemporary religion, 2022)
Through an exercise of decolonial listening, this article works with hijab-wearing women in Lebanon, a small Arab-majority confessional country, to voice, conceptualise, and analyse their lived experience within ‘mainstream Lebanese society’. Investigating their ‘social form’, it advances this lived experience as a belated Arabo-Islamic difference in excess, with a ‘wounded habitus’. Accordingly, it argues that a racialisation due to wearing the hijab is experienced through exclusion from citizenry, modernity, and, most violently, humanity. The article thus showcases religion (Islam) as a persistent key nexus of exclusion where imagined national identities, global coloniality, and Empire entwine to enforce a pervasive experience of dehumanising subordination for the erasure of modernity’s (religious, Muslim) Other.